Mathematical Communication Ability across Learning Styles: A Systematic Review and a Differentiated Instructional Framework - Charis Maulana; Alim Jaizul (International Journal of Ethno-Sciences and Education Research, 2026)
Mathematical communication is one of the core competencies students need in order to interpret, represent, and justify mathematical ideas, yet Indonesian students' performance on international literacy assessments such as the Programme for International Student Assessment (PISA) has remained persistently below the international average. Prior research has repeatedly linked this gap to students' learning styles – visual, auditory, and kinesthetic – but existing reviews mostly stop at describing which style performs comparatively better, without translating the findings into concrete instructional guidance and without accounting for the growing use of technology-integrated mathematics instruction. This study addresses that gap through a systematic literature review of empirical studies published between 2017 and 2025, retrieved from Google Scholar and SINTA-accredited Indonesian journal databases using the keywords "mathematical communication ability" and "learning style". Twenty-one empirical studies met the inclusion criteria of thematic relevance, full-text accessibility, and indexing status, and were analyzed using narrative synthesis against four communication indicators adapted from established mathematical-communication assessment literature. The review confirms that no single learning style consistently outperforms the others in mathematical communication; each style instead shows a distinctive profile of strengths and weaknesses across the indicators of translating everyday situations into mathematical symbols, representing ideas through diagrams, using correct mathematical notation, and drawing logical conclusions. The review further finds that technology-integrated and task-design approaches can narrow style-based gaps when tasks are deliberately aligned with a style's dominant sensory channel. Building on these findings, this paper proposes a Differentiated Instructional Framework that maps concrete, style-matched intervention strategies onto the weaknesses identified for each learning style, offering teachers and curriculum developers a practical, literature-grounded starting point for designing differentiated mathematics instruction.